2001
DOI: 10.1007/bf03019751
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative intravenous flurbiprofen reduces postoperative pain after abdominal hysterectomy

Abstract: GENERAL ANESTHESIAPurpose: To assess whether perioperative intravenous administration of flurbiprofen, a non-steroidal anti-inflammatory drug, reduced postoperative pain after abdominal hysterectomy.Methods: Forty-five patients undergoing abdominal hysterectomy were randomly assigned to one of three groups of equal size. A control group (CONT) received a placebo 30 min before and at the end of surgery. The other two groups, PRE and POST, received 1 mg·kg -1 flurbiprofen iv 30 min before and at the end of surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 10 publications
0
22
1
Order By: Relevance
“…Our previous study confirmed that preoperative administration of flurbiprofen axetil in patients scheduled to undergo thoracotomy exerts marked preemptive analgesic effects [4]. Prophylactic administration of this drug before operation can effectively reduce the degree of postoperative pain and the requirement for analgesic drugs [3,5]. NSAIDs and opioid drugs are known to possess synergistic analgesic effects.…”
Section: Introductionmentioning
confidence: 65%
“…Our previous study confirmed that preoperative administration of flurbiprofen axetil in patients scheduled to undergo thoracotomy exerts marked preemptive analgesic effects [4]. Prophylactic administration of this drug before operation can effectively reduce the degree of postoperative pain and the requirement for analgesic drugs [3,5]. NSAIDs and opioid drugs are known to possess synergistic analgesic effects.…”
Section: Introductionmentioning
confidence: 65%
“…The improvement in pain control is likely the result of perioperative CoX inhibition. [12][13][14][15][16]19 Reduction of PG synthesis would be expected to diminish nociceptor sensitization and inflammatory responses that normally accompany movement and stretching of injured tissues. [25][26][27] The CoX selectivity of FA remains unclear, although it was Data are mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
“…28 In the present study, the dose of FA was adopted on the basis of values reported in the literature. 13,14 Since the analgesic effect of FA usually begins 30 min after administration, with an elimination half-life of six hours, we administered FA 30 min before and six hours after skin incision in the FA group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…before propofol injection [5]. Various propofol formulations in mixtures of medium-chain triglyceride (MCT) and long-chain triglyceride (LCT) (propofol MCT/LCT) induces less injection pain than the original propofol formulation (propofol LCT) [10], but even these trials could not completely abolish the pain.Flurbiprofen, a nonsteroidal antiinflammatory drug (NSAID), administered before surgery was reported to have a postoperative analgesic effect (i.e., preemptive analgesic effect) [11]. Therefore, if prior administration of flurbiprofen could decrease propofol injection pain, this method would have double benefits: decreased propofol injection pain and preemptive analgesia.…”
mentioning
confidence: 98%